Secondary schools One Health training of trainers: One Health education initiative for pastoralist students in Somalia - Hared, Y.A.; Abdullahi, S. (International Livestock Research Institute, 2025)
The One Health Education Initiative for pastoralist students in Somalia aims to address critical health education gaps within Somali pastoralist communities by incorporating One Health principles into secondary school curricula in the Awdal and Benadir regions. The initiative focuses on equipping teachers with the necessary knowledge and tools to educate students on vital health topics such as hygiene, disease prevention, and safe human-animal interactions. It will achieve this by developing a comprehensive facilitator manual tailored to pastoral settings, organizing teacher training workshops, and creating a monitoring framework to track the integration of One Health concepts over six months.